International conference on terrain and geohazard challenges facing onshore oil and gas pipelines evaluation, routing, design, construction, operation - Sweeney, Mike (Geotechnical engineer) (Thomas Telford, 2005)
The objectives of the conference and this volume are: to share new thinking, to promote an engagement between pipeline designers, builders and operators, geoengineering and environmental specialists and client organisations; and to provide a library of exemplars of good practice.
Proceedings of a three day international conference ... organised by the Instituition of Civil Engineers in association with BP Exploration and held at the Institution of Civil Engineers, London, UK, on 2-4 June 2004.
Keywords: Pipelines -- Congresses.; Pipelines -- Design and construction -- Congresses.; Pipelines -- Environmental aspects -- Congresses.; Petroleum industry and trade -- Risk assessment -- Congresses.; elektronické knihy; electronic books